2005
DOI: 10.1121/1.2047127
|View full text |Cite
|
Sign up to set email alerts
|

Optimal virtual sensing for active noise control in a rigid-walled acoustic duct

Abstract: The performance of local active noise control systems is generally limited by the small sizes of the zones of quiet created at the error sensors. This is often exacerbated by the fact that the error sensors cannot always be located close to an observer's ears. Virtual sensing is a method that can move the zone of quiet away from the physical location of the transducers to a desired location, such as an observer's ear. In this article, analytical expressions are derived for optimal virtual sensing in a rigid-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This sensing method involves estimating the sound field at a location remote from the physical sensors and using an active control system to minimise the sound field at the remote location. There have been a number of excellent papers published on this topic [13][14][15][16] and more recently, the technique has been extended to using fixed microphones to generate a moving virtual microphone [17][18][19][20] . Why is a virtual microphone of interest?…”
Section: G Virtual Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…This sensing method involves estimating the sound field at a location remote from the physical sensors and using an active control system to minimise the sound field at the remote location. There have been a number of excellent papers published on this topic [13][14][15][16] and more recently, the technique has been extended to using fixed microphones to generate a moving virtual microphone [17][18][19][20] . Why is a virtual microphone of interest?…”
Section: G Virtual Sensingmentioning
confidence: 99%
“…Thus it is necessary for the virtual microphone to be capable of moving with the subject's ear. The location of the ear in 3-D space can be determined using ultrasound 18 , much like some cameras do when focussing automatically.…”
Section: G Virtual Sensingmentioning
confidence: 99%
“…15 Peterson et al investigated the virtual error sensing in a rigid-walled acoustic duct and found that theoretically it is possible to obtain infinite reductions at virtual locations and this can be extended to create a moving quiet zone, but the noise reduction will decrease for high excitation frequencies and larger virtual distances. 16,17 Petersen et al proposed a virtual sensing algorithm for local active noise control systems using Kalman filtering theory and demonstrated its effectiveness by implementing the algorithm on an acoustic duct arrangement. 18 A problem with the virtual error sensor arrangement is that it requires preliminary identification of the system.…”
Section: Introductionmentioning
confidence: 99%